Correlation between farmers’ income and social changes case study in Kawangkoan District and Tareran District, Minahasa Regency, North Sulawesi Province, Indonesia - Kalangi, Joula S.; Kalalo, Rieneke R. (International research journal of management, IT and social sciences, 2022)
This research is about how the occurrence of social changes in society in relation to farmers’ income, so the problem was to find out the extent to which farmers’ income related to social change. The aim was to analyze the relationship between farmers’ income and social changes that occurred in two sub-districts, namely Kawangkoan and Tareran. The population in this study was taken from farmer families who got their income from agricultural products amounting to 626 households and then determined the samples from 125 families. By using the quantitative analysis technique of product-moment correlation, the results showed the magnitude of the correlation coefficient which was developed into a coefficient of determination than the interpretation of r2 = 0.9216 or 92.16% explained that an increase in the income of 1 unit would be followed by an increase in social change of 0.9216. In other words, the increase in farmers’ income by 1% would increase the social change by 92.16%. From the results above, it is clear that it supports the formulation of the hypothesis that there is a positive relationship between farmers’ income with social changes in the community.